The effect of rating errors towards the effectiveness of performance appraisal - Sabrina, Nasser Khan (Universiti Malaysia Sarawak, UNIMAS, 2009)
The aim of this research is to study the effect of rating errors towards the effectiveness of performance appraisal. The organization that is chosen for this study is one of the state secretaries in Malaysia. Interview is used to collect all of the required data. This research studies the informants knowledge on rating errors, the effect of halo effect, leniency and central tendency towards the effectiveness of performance appraisal and ways that could be taken to solve and prevent rating errors. The findings of this study state that rating errors such as halo effect, leniency and central tendency has a negative effect towards the effectiveness of performance appraisal. Some recommendations that have been identified are to conduct training to the raters in the organization so that they would have a full understanding about rating errors and take steps of measurements to avoid rating biases and inaccuracies. Employee feedback is also another way to avoid rating errors because employees can give their opinions and comments on their rating results. The raters can know the reason why the employees perform or not perform a particular act. Future researchers can use the information and findings of the errors mentioned in this study to continue conducting study on those errors for more helpful results. In conclusion, this research would benefit the employees and the organization because rating errors only bring more harm than good. The avoidance of rating errors would lead the employees to increase the organization’s productivity because they would be satisfied with their evaluation results, thus increase their effort to bring more benefit to the organization.